Chikungunya-associated encephalitis with postencephalitic parkinsonism in an elderly woman: a case report - Islam, Md Rashedul; Rahman, Tanbin; Islam, Jahidul; Khan, Mohammed Sakhawat Hossen; Hasan, Sohali; Tushar, Mazadul Kabir (BIRDEM Medical Journal, 2026)
Chikungunya virus infection usually manifests with fever, rash, and arthralgia, but neurological involvement is rare and post-encephalitic parkinsonism is exceptionally uncommon. We report a 70-year-old diabetic, hypertensive woman who developed altered consciousness after febrile illness and polyarthritis during a chikungunya outbreak. Magnetic Resonance Imaging of brain revealed bilateral basal ganglia hyperintensities with diffusion restriction, and cerebrospinal fluid analysis showed lymphocytic pleocytosis, elevated protein, and chikungunya viral polymerase chain reaction positivity. She improved with intravenous immunoglobulin, but subsequently developed parkinsonian features one month later, consistent with post-encephalitic Parkinsonism, which responded to Dopaminergic therapy. This case highlights that chikungunya virus can rarely cause central nervous system involvement with delayed parkinsonism, underscoring the need for early recognition, immunotherapy, and long-term neurological follow-up. BIRDEM Med J 2026; 16(1): 36-39